2002
DOI: 10.1080/01443610120101781
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health hazards among health care workers in an obstetrics and gynaecology unit of a Nigerian teaching hospital

Abstract: The occupational health hazards among health-care workers in an obstetrics and gynaecology unit were investigated. A total of 78 pretested questionnaires were administered to the doctors, nurses and ward orderlies in the unit of Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria. The common occupational health hazards were work-related stress (83.3%), needle-stick injuries (75.6%), bloodstains on skin (73.1%), sleep disturbance (42.3%), skin reactions (37.2%) assault from patients (24.3%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 11 publications
4
34
1
Order By: Relevance
“…These results congruent with the study results carried out by Beltrami (2000) and the study done by Wang, Chen & Liu (2010), who concluded that respondents who were had a high level of awareness towards universal precautions. Furthermore, theses study results consistent with the findings reported by Orji (2002), who concluded that non-compliance among medical doctors and nurses are associated with insufficient knowledge, workload, forgetfulness, workplace safety and the insight that colleagues also failed to follow.…”
Section: Discussionsupporting
confidence: 82%
“…These results congruent with the study results carried out by Beltrami (2000) and the study done by Wang, Chen & Liu (2010), who concluded that respondents who were had a high level of awareness towards universal precautions. Furthermore, theses study results consistent with the findings reported by Orji (2002), who concluded that non-compliance among medical doctors and nurses are associated with insufficient knowledge, workload, forgetfulness, workplace safety and the insight that colleagues also failed to follow.…”
Section: Discussionsupporting
confidence: 82%
“…These were also found in some previous studies in America, Britain and Nigeria. (Rosenman et al, 2003, Medina-Ramon et al, 2003, Bello et al, 2009, Imperial College London, 2013, Zock, 2005, Delcos et al, 2006, Orji et al, 2002 The skin lesions may have resulted from insect bite to which these workers are exposed to especially when they are on night shifts while the asthmatic symptoms are due their exposure to dusty particles while doing their work. Other health problems found in this study which were not reported in previous studies include eye problems, burns and upper respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the case only in developing countries like Nigeria; even in developed world, these groups of workers are usually taken into cognizance by legislations, and do not have the luxury of accessing available occupational health services which other workers enjoy. (Orji et al, 2002, Ansa et al, 2002, Kirtiganda et al, 2011 The duties of Hospital cleaners include cleaning of patients' rooms, nursing units, surgical areas, administrative offices, laboratory areas, waiting areas and public restrooms. They also clean furniture, polish floors and vacuum carpets.…”
Section: Introductionmentioning
confidence: 99%
“…Chappell and Di Martino 4) document international studies of work-related violence occurring in: Australia, Brazil, Bulgaria, France, Germany, Japan, Lebanon, Portugal, South Africa, Spain, Thailand, the United Kingdom, and the United States. In addition, many studies on workrelated violence also exist outside the previously mentioned locations, including: Canada 5) ; Sweden 6) ; Nigeria 7) ; Jamaica 8) ; Taiwan 9) ; Ireland 10) ; and Turkey 11) . Specific industries or groups of workers appear to be at increased risk for violence.…”
Section: Introductionmentioning
confidence: 99%